(untitled) (Research, Society and Development, 2020)
Obesity has increased dramatically in recente years, becoming a serious public health problem. This study aimed to analyze weight gain during pregnancy, the associated factors and their outcomes. Descriptive, cross-sectional stydy, carried out with women in mediate postpartum, at a reference maternity in the municipality of Maringá-Pr, from 1 to 30 march 2018. Data collection was performed through the records on the pregnant woman´s card, the woman´s and newborn´s medical records and through a structured questionnaire. The variables associated with weight gain during pregnancy were the number of pregnancies (p=0.003) and parity (p=0.041). Women with obesity prior to pregnancy had a higher prevalence of excessive weight gain during pregnancy. Based on the results of the presente study, it is concluded that excessive weight gain during pregnancy was greater among primiparous and primiparous women. Further studies on the subject are suggested to provide subsidies for planning actions aimed at controlling weight gain during pregnancy.